Demographic Changes in Vietnam: Challenges for Old-age Support and Implications for Social Protection Policy - Nguyen Anh, Dang (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
In this article, the author examines an important emerged question of policy and practice on how to adapt effectively to the demographic changes in today’s Vietnam. The dramatic decline of fertility, the demographic bonus, increased mobility, rising longevity and rapid population aging, in particular, have brought in both opportunities and challenges in the next 20 years. As Vietnamese society ages rapidly, the demand for formal aged and long-term care rises as well and there is a need for a more consolidated and coherent policy and reforming the current system of social pension and social protection. The author maintains that the fragmented programs and financing, inadequate services ò ola-age care and support are a barrier to improve the effectiveness of social protection and pension scheme. Many implications and options for policy have been proposed and discussed to overcome the challenges. This will require significant investment, improved outreach, greater harmonization of information systems and development of qualified human resources for old-age care and support.Received 2nd October 2017; Revised 20th October 2017; Accepted 30th October 2017